Miguel de Asúa, Science and Catholicism in Argentina (1750-1960). A Study on Scientific Culture, Religión, and Secularisation in Latín America. Berlin/Boston: de Gruyter, 2022, 365 pp - Amador, Esteban (2022)
Fil: Amador, Esteban. Universidad de Buenos Aires; Argentina